Cardiovascular Risk Assessment and Impact of Medications on Cardiovascular Disease in Inflammatory Bowel Disease. Issue 7 (26th September 2020) - Sinh, Preetika; Cross, Raymond
Abstract: There is increased risk of cardiovascular disease in patients with chronic inflammatory disorders such as rheumatoid arthritis, psoriatic arthritis, and systemic lupus erythematosus. Studies have shown association between cardiovascular disease (eg, myocardial infarction, heart failure, stroke) and inflammatory bowel disease. Medications such as infliximab and adalimumab (monoclonal antibodies to tumor necrosis factor α) may help decrease the inflammatory burden and cardiovascular risk; however, there have been reports of hypertriglyceridemia and worsening of moderate to severe heart failure with these medications. Janus kinase inhibitors, such as tofacitinib, have been associated with hyperlipidemia and thromboembolism. We aim to discuss clinical and imaging modalities to assess cardiovascular risk in inflammatory bowel disease patients and review the role of various medications with respect to cardiovascular disease in this population.